Knowledge Economy’s Externalities and Urban Growth (2021)
Centrality of knowledge-based industries (KBI) in the economy of metropolitan areas leads to the transformation of their labour markets and promotion of new forms of urban growth, because of creation of KBI specialized clusters. KBI are industries that are highly based on codified and tacit knowledge located in people and communities, which become important aspects for spatial employment location. The hypothesis of this paper suggests that, despite high specialization of KBI and their integration into global networks, these industries have functional linkages in regional markets, thus affecting the dynamics of employment growth as a whole. This is verified for Catalonia, in which Barcelona Metropolitan Region (BMR) is the largest urban agglomeration. Methodology includes a Proxscal Multidimensional Scale Analysis that relates an Economic Dependency matrix, which explains the relationship between all the economic sectors with a Spatial Dependency matrix, which weights the size of the localized employment with the inter-municipal distance. Results reveal, firstly, that KBI have intense economic interlinkages with other industries in the Catalonian market, however, these interlinkages do not encourage spatial proximity among them in terms of employment location, which reveals the existence of long-range economic interlinkages; secondly, proximity to metropolitan core evidenced as a key factor for location of KBI’ employment; this is because in those areas firms may access to benefits of network and agglomeration economies, encouraging in this way polycentric growth. Furthermore, paper results offer an attractive and informative data-driven approach to conduct urban analysis studies that may be reproducible in other urban data contexts, to provide solutions in employment growth city planning public policies related.